PERSEPSI ANAK MUDA TERHADAP KEBERADAAN LANSIA DI INDONESIA - Adityo Nugroho (Journal of Urban Sociology, 2019)
Indonesia will experience an increase in the number of elderly in the next few years. This condition will have two implications at once. Being a burden on society and the country, or able to contribute positively. If the elderly continue to be active and can be empowered. This article contains an overview of young people's perceptions of the existence of the elderly. Both in the form of activities, rights, and the role of the state. The study was conducted with an online survey system. Respondents were 347 young people aged 16-30 years. The results showed that young people fully support various activities undertaken by the elderly. But do not understand the rights of the elderly. Young people also demand the participation of the state in efforts to meet the welfare of the elderly. Young people with their characteristics are expected to be able to be involved in protecting the elderly. Keywords: Youth, Elderly, Activities, Rights, State.